Optimization of ski jumping in-run posture using computational fluid dynamics - Wenhan Liu; Feixiang Lu; Xiang Suo; Weidi Tang (Scientific Reports)
Abstract While aerodynamic optimization during ski jumping flight phases is well-studied, critical knowledge gaps persist regarding posture-fluid interactions in the in-run phase – particularly the dominance of drag dynamics over lift enhancement for speed maximization. This study establishes an athlete-specific 3D model to investigate posture-dependent resistance through high-resolution CFD simulations. Systematically analyzing four key posture parameters – torso attack angle (α), thigh attack angle (β), ankle joint angle (γ), and hip abduction angle (ε) – reveals α as the governing factor influencing aerodynamic resistance during acceleration. The optimized configuration ( $$\:\alpha\:\in\:\left[0^\circ\:,2^\circ\:\right]$$ , $$\:\beta\:\in\:\left[20^\circ\:,22^\circ\:\right]$$ , $$\:\gamma\:\in\:\left[43^\circ\:,45^\circ\:\right]$$ , and $$\:\epsilon\:\in\:\left[-2^\circ\:,0^\circ\:\right]$$ ) reduces cumulative air resistance by approximately 5% compared to conventional postures, demonstrating that marginal angular adjustments in torso positioning significantly outweigh other joints’ contributions to drag reduction. Contrary to flight-phase strategies emphasizing lift generation, the results establish drag minimization as the primary in-run optimization objective. These findings provide evidence-based posture guidelines for athletes while advancing a paradigm shift from empirical to physics-driven training methodologies – particularly through computational fluid dynamics with practical sports biomechanics. The work positions CFD as an indispensable tool for quantifying millimeter-scale posture adaptations in winter sports equipment-athlete system optimization.